High-capacity long-circulation single-crystal lithium-rich manganese-based material and preparation method thereof

Through high-temperature solid phase method and cobalt-free design, a high-capacity long-circulating single crystal lithium-manganese-based material was prepared, which solved the problems caused by poor material performance in the prior art and high-temperature calcination, and achieved efficient and low-cost material preparation and excellent electrochemical performance.

CN119640405AInactive Publication Date: 2025-03-18山东诺迅新能源有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510176880.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure CN119640405A_ABST
    Figure CN119640405A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of single-crystal lithium-rich manganese-based materials, in particular to a high-capacity long-circulation single-crystal lithium-rich manganese-based material and a preparation method thereof.The structural general formula of the high-capacity long-circulation single-crystal lithium-rich manganese-based material is Li [NixLi (1 / 3-2x / 3) Mn (2 / 3-x / 3)] O2, and the high-capacity long-circulation single-crystal lithium-rich manganese-based material belongs to a layered structure, the lithium ions are located at interlayer positions, a layered structure formed by transition metal nickel, manganese and oxygen provides channels for the lithium ions, and the content of the lithium element in the material changes according to the value of x and is 0.1 lt; xlt; 0.4 part; the nickel element participates in the gain-loss reaction of electrons, and the valence of the nickel element is + 2 or + 3. Through the cobalt-free design, the problems of poor structure and energy consumption caused by the fact that single crystal materials generally need high-temperature calcination are solved; the high-capacity long-cycle single-crystal lithium-rich manganese-based material has the advantages of high capacity, excellent cycle performance and only need of medium and low temperature synthesis, and is very easy for large-scale commercial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of single crystal lithium-rich manganese-based material preparation, and in particular to a high-capacity, long-cycle single crystal lithium-rich manganese-based material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy lithium battery power storage, high energy density and high safety have become the top priorities in the development and optimization of lithium battery chemical systems.

[0003] The preparation of single crystal materials usually requires long-term calcination at 900°C or even higher temperatures to promote grain growth, which will lead to a large amount of energy consumption and irreversible damage to the material structure at high temperatures. For example, the patent application for a single crystal lithium-rich manganese-based positive electrode active material with preferential growth of crystal faces disclosed in Announcement No. CN118867221A proposes a single crystal lithium-rich manganese-based positive electrode active material with 001 and 100 dominant crystal faces and a long strip shape, but its calcination temperature is still as high as 900°C, which will lead to a poor layered structure, and the cycle performance still does not meet the commercialization needs, and its single crystal particles are still agglomerated. The patent application for a method for preparing doped single crystal lithium-rich manganese-based positive electrode materials by hydrothermal method-molten salt assisted is disclosed in Announcement No. CN116971021A. It is believed that the single crystal morphology is well dispersed, but the hydrothermal method-molten salt assisted preparation will lead to a large amount of energy consumption and high cost, and the process is difficult to commercialize. The single crystalization of materials can effectively increase the compaction density, reduce the internal stress of the material, and inhibit microcracks and structural degradation during the cycle process. Its relatively small specific surface area can alleviate side reactions under high voltage. However, the elemental composition of existing manganese-based lithium battery positive electrode materials is complex and diverse, and in particular, they are doped with a variety of rare element materials. Not only is the preparation cost high, but it is also highly dependent on scarce resources. The existing manganese-based lithium battery positive electrode materials will undergo multiple structural shape changes under the influence of frequent charging and discharging, especially the surface area is prone to softening and collapse, which will seriously limit the capacity and cycle performance of manganese-based lithium battery positive electrode materials. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that it is difficult to prepare high-capacity and long-cycle single-crystal lithium-rich manganese-based materials in the prior art, and to propose a high-capacity and long-cycle single-crystal lithium-rich manganese-based material and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A high-capacity, long-cycle single-crystal lithium-rich manganese-based material, the general structural formula of the high-capacity, long-cycle single-crystal lithium-rich manganese-based material is Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3)]O2, the high-capacity long-cycle single-crystal lithium-rich manganese-based material has a layered structure, lithium ions are in the interlayer position, and the layered structure formed by transition metal nickel, manganese and oxygen provides a channel for lithium ions, wherein: The content of lithium in the material varies according to the value of x, and 0.1 <x<0.4; Nickel participates in the reaction of gaining and losing electrons, and the valence of nickel is +2 or +3; manganese is used to enhance structural stability, and the valence of manganese is +3 or +4; Oxygen is used to provide the skeleton.

[0006] Preferably, the high-capacity, long-cycle single-crystal lithium-rich manganese-based material has a hexagonal prism single-crystal morphology structure, a cobalt-free design, and a particle size D50 of 1-3 μm.

[0007] As described above, a method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material adopts a high-temperature solid phase method, comprising the following steps: Step S1, preparing precursor A1; Step S2, preparing a refined precursor A2; Step S3, preparing a mixture B1; Step S4, preparing a calcined body C1; Step S5, preparing the finished product D1.

[0008] Preferably, the specific process of preparing the precursor A1 in step S1 is as follows: dissolving nickel salt and manganese salt in deionized water in a molar ratio of 1:6.33-1:1.33 to form a salt solution, pumping the salt solution into a stirring kettle loaded with nitrogen, and simultaneously pumping an alkaline solution into the kettle to adjust the pH value to 10-12, stirring at a temperature of 45-65°C until the reaction is complete, and then filtering, washing once, and vacuum drying once to obtain the precursor A1.

[0009] Preferably, the salt solution concentration is 2 mol / L, the alkaline solution is made of sodium hydroxide and ammonia water, and the alkaline solution concentration is 4 mol / L, the stirring speed is 200-500 r / min, and the pH is neutral after complete reaction, the primary vacuum drying temperature is 80-140°C, and the primary vacuum drying time is 4-20h.

[0010] Preferably, the specific process of preparing the refined precursor A2 in step S2 is: adding the precursor A1 to anhydrous ethanol and performing ball milling, and obtaining the refined precursor A2 after drying and grinding once.

[0011] Preferably, the primary drying temperature is 40-90° C., the ball milling speed is 200-800 r / min, and the ball milling time is 1-8 h.

[0012] Preferably, in step S3, the specific process of preparing the mixture B1 is to mix the refined precursor A2, the lithium salt and the auxiliary lithium salt in a molar ratio of 1.1-1.5:1-1.2:0.01-0.03 to obtain the mixture B1.

[0013] Preferably, in step S4, the specific process for preparing the calcined body C1 is that the mixture B1 is subjected to a low-temperature primary calcination, a medium-temperature secondary calcination and a medium-low temperature tertiary calcination to obtain the calcined body C1, the low-temperature primary calcination temperature is 280-350°C, the heating rate is 1-3°C / min, and the calcination time is 3-8h, the medium-temperature secondary calcination temperature is 500-750°C, the heating rate is 4-8°C / min, and the calcination time is 1-3h, the medium-low temperature tertiary calcination temperature is 380-500°C, the heating rate is 2-4°C / min, and the calcination time is 10-20h.

[0014] Preferably, in step S5, the specific process of preparing the finished product D1 is to obtain the high-capacity, long-cycle single-crystal lithium-rich manganese-based material finished product D1 after the calcined body C1 is subjected to secondary washing and secondary vacuum drying, and the secondary vacuum drying temperature is 40-80°C and the secondary vacuum drying time is 4-20h.

[0015] Compared with the prior art, the present invention has the following advantages: 1. The present invention reduces material costs and dependence on scarce resources through cobalt-free design.

[0016] 2. The present invention uses single crystallization to improve the compaction density and structural stability of the material, inhibit microcracks and structural degradation during the life process, reduce the specific surface area and reduce surface side reactions.

[0017] 3. The present invention utilizes auxiliary lithium salt to greatly reduce the calcination temperature in the synthesis process, thereby solving the problems of poor structure and energy consumption caused by the high-temperature calcination generally required for single crystal materials.

[0018] 4. The high-capacity, long-cycle single-crystal lithium-rich manganese-based material of the present invention has the advantages of high capacity, excellent cycle performance and only requires medium and low temperature synthesis, and is very easy to mass-produce commercially. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD diagrams of the positive electrode materials prepared in Example 1, Example 2, and Comparative Example 1; Figure 2 This is a SEM image of the positive electrode material prepared in Example 1; Figure 3 This is a SEM image of the positive electrode material prepared in Example 2; Figure 4 This is a SEM image of the positive electrode material prepared in Comparative Example 1; Figure 5Comparison chart of the first charge-discharge curves of the cathode material prepared in Example 1; Figure 6 Comparison chart of the first charge-discharge curves of the cathode material prepared in Example 2; Figure 7 Comparison chart of the first charge-discharge curves of the cathode material prepared in Comparative Example 1; Figure 8 Comparison chart of the life curves of the cathode materials prepared in Example 1, Example 2, and Comparative Example 1; Fig. 9 Schematic diagram of the single-crystal morphology structure of a high-capacity long-cycle single-crystal lithium-rich manganese-based material proposed by the present invention; Fig.10 Upper cross-sectional schematic diagram of the single-crystal morphology structure of a high-capacity long-cycle single-crystal lithium-rich manganese-based material proposed by the present invention; Fig.11 Side cross-sectional schematic diagram of the single-crystal morphology structure of a high-capacity long-cycle single-crystal lithium-rich manganese-based material proposed by the present invention. Detailed implementation manners

[0020] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.

[0021] Referring to Figure 1-Figure 11 , a high-capacity long-cycle single-crystal lithium-rich manganese-based material, the structural general formula of the high-capacity long-cycle single-crystal lithium-rich manganese-based material is Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) O2. The high-capacity long-cycle single-crystal lithium-rich manganese-based material belongs to a layered structure, and lithium ions are in the interlayer position. The layered structure formed by transition metals nickel and manganese with oxygen provides channels for lithium ions. During the charge-discharge process, lithium ions can reversibly intercalate and deintercalate between the layers. Among them: The content of lithium element in the material varies according to the value of x, and 0.1 < x < 0.4. Overall, it plays a key role in providing charge carriers in the material. As an important part of the material, during the charge-discharge process, lithium ions will reversibly intercalate and deintercalate in the crystal structure, thereby realizing the charge-discharge function of the battery.

[0022] Nickel element participates in the reaction of electron gain and loss, and the valence of nickel element is +2 or +3. It occupies a certain proportion in the material. During the charge-discharge process, the valence state of nickel ions will change, and it can also have an important impact on the electrochemical performance of the material, helping to improve the specific capacity and energy density of the material.

[0023] Manganese is used to enhance structural stability, and the valence of manganese is +3 or +4. It is also one of the key elements in the material. In the electrochemical process, the valence change of manganese ions also plays an important supporting role in the charging and discharging reaction of the battery. At the same time, manganese resources are relatively abundant, which gives the material a certain cost advantage.

[0024] The oxygen element is used to provide a skeleton. It combines with lithium, nickel, manganese and other elements to form a stable crystal structure, providing the necessary environment for the transmission of lithium ions and the valence change of transition metal ions. In the process of charging and discharging, oxygen also participates in some complex chemical reactions, which affects the performance of the material.

[0025] The high-capacity and long-cycle single-crystal lithium-rich manganese-based material has a hexagonal prism single crystal morphology structure, a cobalt-free design, and a particle size D50 of 1-3μm. Different from traditional polycrystalline lithium-rich manganese-based materials, the single-crystal structure gives the material many advantages such as fewer reaction interfaces, high compaction density, strong structural stability, and good safety. Specifically, it has a high theoretical specific capacity, generally exceeding 250mAh / g, which can provide lithium-ion batteries with higher energy density, and can effectively reduce the generation of microcracks caused by particle expansion and contraction during the charge and discharge process, improve the cycle performance of the material, and can maintain a high capacity retention rate after multiple charge and discharge cycles. Compared with ordinary lithium-rich manganese-based materials, the cycle performance is significantly improved, and it can withstand more cycles without obvious capacity decay.

[0026] Further explanation: Although the use of spherical particles has advantages for high-capacity long-cycle single-crystal lithium-rich manganese-based materials, especially in terms of dense packing characteristics, surface energy distribution and isotropy, spherical particles are not stable, and the activities between individuals are offset, making it difficult to provide channels for lithium ions. The hexagonal columnar single crystal morphology structure is adopted according to the dense paving principle. For details, please refer to the attached manual. Fig. 9 -Attached Fig.11 , which helps to improve the space utilization rate of high-capacity, long-cycle single-crystal lithium-rich manganese-based materials by up to 90.69%. When paving closely, the gaps between adjacent graphics are the smallest, which can make the most effective use of the plane space and form a continuous and unified paving effect. When subjected to external force, the force can be more evenly distributed throughout the structure, so it has more structural stability and pressure resistance.

[0027] It should be noted that the specific model specifications need to be selected and determined based on the actual specifications of the device, and the specific selection calculation method adopts the existing technology in this field, so it will not be repeated.

[0028] The preparation method of the above-mentioned high-capacity long-cycle single-crystal lithium-rich manganese-based material adopts a high-temperature solid phase method, that is, a metal salt or metal oxide is used as a precursor, mixed with an excess of lithium salt, and an appropriate amount of flux is added at the same time, and the temperature is kept at a high temperature for a certain period of time to promote the continuous growth of crystal particles. It includes the following steps: First, the precursor A1 is prepared. The specific steps are as follows: dissolve nickel salt and manganese salt in deionized water at a molar ratio of 1:6.33-1:1.33 to form a salt solution, pump the salt solution into a stirring kettle loaded with nitrogen, and simultaneously pump an alkaline solution to adjust the pH value to 10-12, stir at a temperature of 45-65°C until the reaction is complete, and then obtain the precursor A1 after suction filtration, one washing, and one vacuum drying.

[0029] Secondly, a refined precursor A2 is prepared. The specific steps are as follows: the precursor A1 is added to anhydrous ethanol and ball-milled, and the refined precursor A2 is obtained after drying and grinding once.

[0030] Next, a mixture B1 is prepared. The specific process is to mix the refined precursor A2, lithium salt, and auxiliary lithium salt in a molar ratio of 1.1-1.5:1-1.2:0.01-0.03 to obtain the mixture B1.

[0031] Then, a calcined body C1 is prepared. The specific process is that the mixture B1 is calcined once at low temperature, twice at medium temperature, and three times at medium and low temperature to obtain a calcined body C1. The temperature of the first low temperature calcination is 280-350°C, the heating rate is 1-3°C / min, and the calcination time is 3-8h. The temperature of the second medium temperature calcination is 500-750°C, the heating rate is 4-8°C / min, and the calcination time is 1-3h. The temperature of the three medium and low temperature calcinations is 380-500°C, the heating rate is 2-4°C / min, and the calcination time is 10-20h.

[0032] Finally, the finished product D1 is prepared. The specific process is that the calcined body C1 is subjected to secondary washing and secondary vacuum drying to obtain the high-capacity, long-cycle single-crystal lithium-rich manganese-based material finished product D1. The secondary vacuum drying temperature is 40-80°C and the secondary vacuum drying time is 4-20h.

[0033] Further explanation: The concentration of the salt solution used to prepare the precursor A1 is 2 mol / L, the alkaline solution is made of sodium hydroxide and ammonia water, and the concentration of the alkaline solution is 4 mol / L, the stirring speed is 200-500 r / min, and the pH is neutral after complete reaction, the primary vacuum drying temperature is 80-140°C, and the primary vacuum drying time is 4-20h.

[0034] The primary drying temperature is 40-90°C, the ball milling speed is 200-800r / min, and the ball milling time is 1-8h.

[0035] It should be noted that two examples and one comparative example were carried out to explore the rationality of the preparation method of high-capacity long-cycle single-crystal lithium-rich manganese-based materials:

[0036] Embodiment 1: Nickel chloride and manganese chloride were dissolved in deionized water at a molar ratio of 1:2.33 to form a 2 mol / L salt solution, and the solution was then pumped into a stirred tank with nitrogen, and a 4 mol / L alkaline solution prepared by sodium hydroxide and ammonia water was simultaneously pumped in to adjust the pH value to 11, and the reaction was completed at 60°C and a stirring speed of 300 r / min, and the precursor A1 was obtained after suction filtration and washing once until the pH of the washing liquid was neutral, and then vacuum dried at 100°C for 15 h to obtain the precursor A1; Precursor A1 was added with anhydrous ethanol and ball-milled at a speed of 300 r / min for 7 h, placed in a 60°C forced air drying oven for drying, and then ground to obtain a refined precursor A2; The lithium salt lithium carbonate and the refined precursor A2 are mixed in a molar ratio of 1.4:1 and the lithium salt lithium hydroxide and the auxiliary lithium salt lithium bicarbonate are mixed in a molar ratio of 1:0.03 to obtain a mixture B1; The mixture B1 was calcined at 550°C for 8 h (heating rate of 2°C / min), and then calcined at 950°C for 14 h (heating rate of 5°C / min) to obtain calcined body C1. The calcined body C1 was washed twice until the pH of the washing liquid was neutral, and then vacuum dried twice at 70° C. for 6 h to obtain a single crystal lithium-rich manganese-based material product D1.

[0037] Refer to the instruction manual Figure 1 , Attachment Figure 2 , Attachment Figure 5 With attached Figure 8 : The high-capacity, long-cycle single-crystal lithium-rich manganese-based material prepared in Example 1 is pure phase and has no other impurity peaks. The (003) to (104) peak ratio is as high as 1.69, proving that the single-crystal material synthesized at a lower temperature has a very good layered structure; the single crystal morphology of the prepared material is obviously regular and uniformly dispersed; the prepared material has an initial discharge capacity of up to 262.99 mAh / g at 0.1C within a voltage range of 2.0-4.8 V; the prepared material has a capacity retention rate of 98.32% after 185 cycles at a charge and discharge rate of 1C / 1C within a voltage range of 2.0-4.8 V, and the cycle performance is very excellent.

[0038] Embodiment 2: Nickel chloride and manganese chloride were dissolved in deionized water at a molar ratio of 1:2.33 to form a 2 mol / L salt solution, and the solution was then pumped into a stirred tank with nitrogen, and a 4 mol / L alkaline solution prepared by sodium hydroxide and ammonia water was simultaneously pumped in to adjust the pH value to 11, and the reaction was completed at 60°C and a stirring speed of 300 r / min, and the precursor A1 was obtained after suction filtration and washing once until the pH of the washing liquid was neutral, and then vacuum dried at 100°C for 15 h to obtain the precursor A1; Precursor A1 was added with anhydrous ethanol and ball-milled at a speed of 300 r / min for 7 h, placed in a 60°C forced air drying oven for drying, and then ground to obtain a refined precursor A2; The lithium salt lithium carbonate and the refined precursor A2 are mixed in a molar ratio of 1.4:1 and the lithium salt lithium hydroxide and the auxiliary lithium salt lithium bicarbonate are mixed in a molar ratio of 1:0.03 to obtain a mixture B1; The mixture B1 was calcined at a low temperature of 300°C for 5 h (heating rate of 2°C / min), then calcined at a medium temperature of 650°C for 4 h (heating rate of 5°C / min), and then calcined at a medium and low temperature of 400°C for 16 h (heating rate of 2°C / min) to obtain a calcined body C1; The calcined body C1 was washed twice until the pH of the washing liquid was neutral, and then vacuum dried twice at 60° C. for 4 h to obtain a single crystal lithium-rich manganese-based material product D1.

[0039] Refer to the instruction manual Figure 1 , Attachment Figure 3 , Attachment Figure 6 , and attached Figure 8 The high-capacity, long-cycle single-crystal lithium-rich manganese-based material prepared in Example 2 is pure phase and has no other impurity peaks. The (003) to (104) peak ratio is as high as 1.58, which proves that the single-crystal material synthesized at a lower temperature has a very good layered structure; the single crystal morphology of the prepared material is obviously regular and uniformly dispersed; the prepared material has an initial discharge capacity of 264.23 mAh / g at 0.1C within a voltage range of 2.0-4.8 V; the prepared material has a capacity retention rate of 97.18% after 144 cycles at a charge and discharge rate of 1C / 1C within a voltage range of 2.0-4.8 V, and the cycle performance is very excellent.

[0040] Comparative Example 1: Nickel chloride and manganese chloride were dissolved in deionized water at a molar ratio of 1:2.33 to form a 2 mol / L salt solution, and the solution was then pumped into a stirred tank with nitrogen, and a 4 mol / L alkaline solution prepared by sodium hydroxide and ammonia water was simultaneously pumped in to adjust the pH value to 11, and the reaction was completed at 60°C and a stirring speed of 300 r / min, and the precursor A1 was obtained after suction filtration and washing once until the pH of the washing liquid was neutral, and then vacuum dried at 100°C for 15 h to obtain the precursor A1; Precursor A1 was added with anhydrous ethanol and ball-milled at a speed of 300 r / min for 7 h, placed in a 60°C forced air drying oven for drying, and then ground to obtain a refined precursor A2; Mixing lithium salt lithium carbonate and refined precursor A2 at a molar ratio of 1.4:1 to obtain a mixture B1; The mixture B1 was calcined at 550°C for 8 h (heating rate of 2°C / min), and then calcined at 950°C for 4 h (heating rate of 5°C / min) to obtain calcined body C1. The calcined body C1 was washed twice until the pH of the washing liquid was neutral, and then vacuum dried twice at 70° C. for 6 h to obtain a single crystal lithium-rich manganese-based material product D1.

[0041] Refer to the instruction manual Figure 1 , Attachment Figure 4 , Attachment Figure 7 With attached Figure 8 The high-capacity and long-cycle single-crystal lithium-rich manganese-based material prepared in Comparative Example 1 is a pure phase without other impurity peaks, but the (003) to (104) peak ratio is only 1.03, which proves that the crystal layered structure of the single-crystal material synthesized at a higher temperature has been destroyed and the mixing is serious; although the prepared material presents a certain single crystal morphology, it is seriously agglomerated; the prepared material has a 0.1C first discharge capacity of up to 215.76mAh / g within a voltage range of 2.0-4.8V, which is much lower than the material performance presented in Example 1 and Example 2; the prepared material has a capacity retention rate of only 87.27% after 114 cycles at a charge and discharge rate of 1C / 1C within a voltage range of 2.0-4.8V, and the cycle performance is much lower than the material performance presented in Example 1 and Example 2, and cannot meet commercial applications.

[0042] When comparing the materials prepared in Example 1, Example 2 and Comparative Example 1, it was found that:

[0043] In summary, the comparison between Example 1, Example 2 and Comparative Example 1 shows that: First, the high-capacity, long-cycle single-crystal lithium-rich manganese-based material has a complete crystal structure, no impurities, and a very regular internal layered structure; Second, the single crystals of Examples 1 and 2 have regular morphologies and are evenly dispersed, while the comparative example 1 synthesized at high temperature presents an agglomerated morphology; Third, the capacity of Example 1 and Example 2 is relatively high, which is 262.99 and 264.23 mAh / g respectively, which is much higher than 215.76 mAh / g obtained in Comparative Example 1; Fourth, from the cycle comparison between Example 1, Example 2 and Comparative Example 1, it can be seen that the high-capacity, long-cycle single-crystal lithium-rich manganese-based material has excellent cycle performance and effectively suppresses microcracks and structural degradation during the life process.

[0044] Therefore, high-capacity, long-cycle single-crystal lithium-rich manganese-based materials have the advantages of high capacity, excellent cycle performance, and only require medium and low temperature synthesis, and are very easy to produce on a large scale commercially.

[0045] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high-capacity, long-cycle single-crystal lithium-rich manganese-based material, characterized in that: The general structural formula of the high-capacity, long-cycle single-crystal lithium-rich manganese-based material is Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) ]O2, the high-capacity long-cycle single-crystal lithium-rich manganese-based material has a layered structure, lithium ions are in the interlayer position, and the layered structure formed by transition metal nickel, manganese and oxygen provides a channel for lithium ions, wherein: The content of lithium in the material varies according to the value of x, and 0.1 <x<0.4; Nickel participates in the reaction of gaining and losing electrons, and the valence of nickel is +2 or +3; Manganese is used to enhance structural stability, and the valence of manganese is +3 or +4; Oxygen is used to provide the skeleton.

2. A high capacity, long cycle single crystal lithium-rich manganese-based material according to claim 1, characterized in that: The high-capacity, long-cycle single-crystal lithium-rich manganese-based material has a hexagonal columnar single-crystal morphology structure, a cobalt-free design, and a particle size D50 of 1-3 μm.

3. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 2, characterized in that: The preparation method adopts a high temperature solid phase method and comprises the following steps: Step S1, preparing precursor A1; Step S2, preparing a refined precursor A2; Step S3, preparing a mixture B1; Step S4, preparing a calcined body C1; Step S5, preparing the finished product D1.

4. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 3, characterized in that: The specific process of preparing the precursor A1 in step S1 is as follows: dissolving nickel salt and manganese salt in deionized water at a molar ratio of 1:6.33-1:1.33 to form a salt solution, pumping the salt solution into a stirring kettle loaded with nitrogen, and simultaneously pumping an alkaline solution to adjust the pH value to 10-12, stirring at a temperature of 45-65°C until the reaction is complete, and then filtering, washing once, and vacuum drying once to obtain the precursor A1.

5. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 4, characterized in that: The salt solution has a concentration of 2 mol / L, the alkaline solution is made of sodium hydroxide and ammonia water, and the alkaline solution has a concentration of 4 mol / L, the stirring speed is 200-500 r / min, and the pH is neutral after complete reaction, the primary vacuum drying temperature is 80-140° C., and the primary vacuum drying time is 4-20 h.

6. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 5, characterized in that: The specific process of step S2, preparing the refined precursor A2, is as follows: adding the precursor A1 to anhydrous ethanol and performing ball milling, and obtaining the refined precursor A2 after drying and grinding once.

7. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 6, characterized in that: The primary drying temperature is 40-90° C., the ball milling speed is 200-800 r / min, and the ball milling time is 1-8 h.

8. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 7, characterized in that: The specific process of preparing the mixed body B1 in step S3 is as follows: the refined precursor A2, the lithium salt, and the auxiliary lithium salt are mixed in a molar ratio of 1.1-1.5:1-1.2:0.01-0.03 to obtain the mixed body B1.

9. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 8, characterized in that: The specific process of preparing the calcined body C1 in step S4 is as follows: the mixture B1 is subjected to low-temperature primary calcination, medium-temperature secondary calcination and medium-low temperature tertiary calcination to obtain the calcined body C1, the low-temperature primary calcination temperature is 280-350°C, the heating rate is 1-3°C / min, and the calcination time is 3-8h, the medium-temperature secondary calcination temperature is 500-750°C, the heating rate is 4-8°C / min, and the calcination time is 1-3h, the medium-low temperature tertiary calcination temperature is 380-500°C, the heating rate is 2-4°C / min, and the calcination time is 10-20h.

10. The method for preparing a high-capacity, long-cycle single-crystal lithium-rich manganese-based material according to claim 9, characterized in that: The specific process of preparing the finished product D1 in step S5 is as follows: the calcined body C1 is subjected to secondary washing and secondary vacuum drying to obtain the high-capacity, long-cycle single-crystal lithium-rich manganese-based material finished product D1, the secondary vacuum drying temperature is 40-80°C, and the secondary vacuum drying time is 4-20h.

Citation Information

Patent Citations

  • High-rate lithium-rich manganese-based positive electrode material monocrystal and preparation method thereof

    CN109537054A

  • Preparation method of lithium-rich manganese-based precursor and positive electrode material and precursor and material

    CN110980818A

  • Single-crystal high-nickel ternary positive electrode material for high-voltage lithium ion battery and preparation method of single-crystal high-nickel ternary positive electrode material

    CN116750810A

  • Cobalt-free lithium-rich manganese single crystal material and preparation method thereof

    CN117779195A

  • Cobalt-free lithium-rich single-crystal positive electrode material with adjustable crystal face and preparation method and application thereof

    CN118800898A